(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article provides a comprehensive scholarly analysis of the artistic and biographical parallels between the novel The Moon and Sixpence by Somerset William Maugham and the life of the French post-impressionist painter Paul Gauguin. The study focuses on the similarities and differences between the fictional character Charles Strickland and Gauguin’s personality, as well as on the process of artistic transformation. The article examines how real-life material is transformed in the creation of a literary character and enriched through the author’s aesthetic vision and philosophical concepts. It also analyzes the artist’s alienation from society, aspiration for inner freedom, and psychological suffering from the perspective of existentialism. The study concludes that the character of Strickland, although based on a real prototype, is elevated to the level of a universal philosophical model.